2017
DOI: 10.1016/j.toxlet.2017.05.015
|View full text |Cite
|
Sign up to set email alerts
|

Induction of proteotoxic stress by the mycotoxin patulin

Abstract: Patulin is a naturally occurring mycotoxin produced by a number of molds and may contaminate a wide variety of food products. In practice, patulin’s main societal relevance concerns apple juice and its products. Multiple advisory bodies, including the U.S. Food and Drug Administration and the World Health Organization, recommend that producers monitor and limit patulin levels in apple juice products. The mechanism of patulin toxicity remains largely unknown. Here we show that patulin induces proteotoxic stress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 33 publications
(58 reference statements)
1
14
0
Order By: Relevance
“…This experiment was carried out in the pdr5Δ mutant background to increase the intracellular levels of bortezomib. Note that arsenic alone induces strong proteotoxic effects, as indicated by the increase in both high-molecular-weight ubiquitinated material and Tmc1 (compare the first and second lanes), consistent with prior reports (24,49). Numbers on the left are molecular masses (in kilodaltons).…”
Section: Fig 2 Vacuolar Degradation Mediates Arsenic-induced Glucose supporting
confidence: 87%
“…This experiment was carried out in the pdr5Δ mutant background to increase the intracellular levels of bortezomib. Note that arsenic alone induces strong proteotoxic effects, as indicated by the increase in both high-molecular-weight ubiquitinated material and Tmc1 (compare the first and second lanes), consistent with prior reports (24,49). Numbers on the left are molecular masses (in kilodaltons).…”
Section: Fig 2 Vacuolar Degradation Mediates Arsenic-induced Glucose supporting
confidence: 87%
“…The effect of PAT in eukaryotic cells has been largely studied [25]. PAT is a strong electrophile which is able to interact with different types of macromolecules, among which PAT is highly reactive with free thiol groups, such as those contained in cysteine residues [44]. Interestingly, in response to PAT, the WE isolate induced the expression of several genes involved in different steps of glutathione, methionine and cysteine biosynthesis, such as those conforming the sulfur assimilation pathway MET3 , MET14 , MET16 , MET5 , MET10 and MET17 (Figure 7).…”
Section: Discussionmentioning
confidence: 99%
“…In that work, the laboratory strain S288c was used, which is genetically closer to WE lineage than to the WA. In addition, a recent report showed that PAT strongly induces the gene RPN2 , whose expression is known to be positively correlated with 20s proteasome activity; suggesting that PAT has a proteotoxic effect [44]. However, this gene was not among those DEGs either in the WE or WA strains.…”
Section: Discussionmentioning
confidence: 99%
“…Patulin is produced in a 10-step biosynthetic pathway that is controlled by 15 genes (Puel et al, 2010;Li et al, 2019). Mice that received an intraperitoneal injection of patulin (1 mg/kg body weight) exhibited a significant increase in the level of ROS in hepatic tissue (Song et al, 2014;Guerra-Moreno and Hanna, 2017;Sun et al, 2018) while 2 µM patulin induced autophagy in HepG2 liver cells in vitro (Sun et al, 2018), suggesting that patulin may have a detrimental impact on liver function in addition to immunotoxicity.…”
Section: Patulinmentioning
confidence: 99%